Characterization of Salmonella Enteritidis isolated from foods and patients in northern Morocco - Sanae Ammari; Amin Laglaoui; Latifa En-nanei; Sophie Bertrand; Christa Wildemauwe; Mohammed Abid (Journal of Infection in Developing Countries)
Objectives: This study aimed to investigate Salmonella Enteritidis strains isolated from human and food sources in the north of Morocco by means of phenotypic and genotypic methods.